The terrible truth about time - "Arnold. Nick" (Scholastic London, 2009)
This work helps you find out what happens if you go too close to a black hole and how flies tell the time. With a fantastic new cover look and extraorrible bits at the back of the book, this best-selling title is sure to be a huge hit with a new generation of "Horrible Science" readers